Legal Aspects of Ownership of Medical Records Documents as Objects of Material Property Rights for Hospitals - Vira Komala; Edi Setiadi; Sri Ratna Suminar (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
Article 297 paragraph (1) of Law Number 17 of 2023 concerning Health explains that medical record documents belong to health service facilities. This has legal consequences for hospitals to maintain the security, integrity, and confidentiality of medical records. However, patients still assume they are the owners of the contents of the records, so violations often occur in disclosing medical records which are not by the provisions. In the Indonesian legal system, ownership of property rights, according to Article 499 BW, is known as the term material which includes the meaning of goods and rights that property rights can control. With this background, the research aims to determine the legal aspects of ownership of medical record documents as objects of property rights for hospitals, so that disclosure of information contained in medical record documents is carried out by applicable legal provisions. The approach method used is normative juridical, the research specifications in this study are analytical descriptive. The data collection technique in this research is literature study and the analysis method in the research uses qualitative analysis methods. The research results prove that medical records can be classified as objects or goods (tangible objects). When referring to the grouping of objects, medical records can be categorized as movable objects. Medical records as movable objects can be owned by the party in charge of the property rights so that whoever controls the object is considered the owner as regulated in Article 1977 of the Civil Code.